IMPLEMENTATION OF STRATEGIC MANAGEMENT TOWARDS QUALITY SCHOOLS - Sholeh, Habib; Metroyadi; Rizalie, Ahmad Muhyani (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
According to studies, strategic management has a significant influence on schools and is considered an essential method used to achieve quality education. The purpose of this research, therefore, is to provide in-depth knowledge of strategic planning, implementation, evaluation, and achievement. This research uses a qualitative multi-site study approach, with data obtained from interviews, observations, and documentation. Furthermore, the sample study was selected through purposive techniques and snowball sampling, with a single case and cross-site used for its analysis. This research shows that schools implemented strategic management to improve its quality following the procedures. Therefore, it is recommended for schools in Muhammadiyah to utilize it in its advancement